A study on the determinants of saving in Malaysia / Nurul Wahidah Md Razi - Md Razi, Nurul Wahidah (Faculty of Business and Management, 2015)
The rapid demographic shift in Malaysia is expected to raise both micro and macro-economic issues. On the microeconomic front, health care, housing, and other related services for the purpose of improving the welfare of the elderly need to be addressed. In addition, macroeconomic issues related to saving, labor productivity, and capital flows also need to receive attention. Due to the inadequacy of recent and comprehensive data and information regarding the behavior of household savers through time, the study designed to increase savings interest. So, this research is to study about what actually the determinants that influences saving behavior in Malaysia. It conducts to determine is there relationship between of income, rate of return, inflation and consumption on saving in Malaysia.